The Effectiveness of Drive-Thru Service Implementation in Increasing Motor Vehicle Tax Revenue at Samsat Soekarno Hatta, Bandung City - Diza Khaerunnisa; Arimbi Triswastika; Candra Mecca Sufyana (Siber Nusantara Research, 2026)
Amidst the rapid development of technology and increasing public mobility, public services are expected to become faster, more practical, and aligned with community needs. One such innovation introduced to meet this demand is the Drive Thru service at Samsat Soekarno Hatta, Bandung. This study aims to assess the effectiveness of the service in improving the collection of Motor Vehicle Tax (PKB). Using a quantitative approach and simple linear regression analysis, data were collected through direct observation, questionnaires distributed to taxpayers, and documentation of tax revenue over the past two years. The results show that the Drive Thru service has a positive impact on the ease of tax payment and significantly contributes to increasing PKB revenue. This innovation demonstrates that fast, efficient, and convenient services can encourage taxpayer compliance and enhance public trust in government service systems. Therefore, the Drive Thru service deserves to be considered a model for modern service delivery in support of technology-based bureaucratic reform.